Perancangan Backend Pada Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) SMK Bina Mandiri Al Qodiriyah Srono - Fitriani, Wandha Dese; Hidayat, Alfin; Suardinata, I Wayan (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
PPDB (Student Admission Selection) is one of the components of student management within an educational institution. PPDB, with all its systems, is carried out to understand and measure school inputs to assist in school development and is expected to make a significant contribution to planning and implementing educational and training activities in the future. The selection process for new students at SMK Bina Mandiri Al Qodiriyah is still conventional, using ledger records to manage prospective students. Therefore, an application is needed to facilitate and expedite the new student admission process at SMK Bina Mandiri Al Qodiriyah. This application is built using the Laravel 9 framework with PHP programming and MySQL database. The features of this application include online student registration. The educational SIM development method is Rapid Application Development (RAD).